Elevation–diversity patterns through space and time: ant communities of the Maloti‐Drakensberg Mountains of southern Africa. (24th June 2014) - Bishop, Tom R.; Robertson, Mark P.; van Rensburg, Berndt J.; Parr, Catherine L.; Gillman, Len
Abstract Aim Patterns of biological diversity are often investigated across space but little work has attempted to explore the consistency of such observations through time. Here, our aim was to understand the patterns of diversity for a functionally critical taxon, the ants (Hymenoptera: Formicidae), through space and time using an extensive dataset collected across an elevational gradient. In addition, we evaluated the importance of two key postulated drivers of elevational diversity patterns: temperature and available area. Location The Maloti‐Drakensberg Mountains of southern Africa. Methods We sampled epigaeic ant communities biannually for 7 years (2006–2012) at eight different elevational sites. We then used an information theoretic approach combined with generalized linear mixed models to: (1) describe diversity patterns through space and time; (2) assess the importance of different abiotic drivers; and (3) understand how much spatio‐temporal variation can be explained by these drivers. Simple regression approaches were also used to test for differences in seasonal variation along the elevational gradient. Results We found clear mid‐elevational peaks of species density and evenness measures. Abundance patterns were complex. The spatial distributions of all three metrics changed across seasons and years. Temperature variables had important roles in explaining both species density and abundance patterns, whilst species density was also influenced by available area. In conjunction, we found much greater seasonal variability in species density at low elevations. This variation was independent of differences in species pool size. Main conclusions We found patterns of ant diversity that are strongly modulated by temporal change. There was a consistent and strong signature of seasonality on the elevation–diversity patterns of the ants, whilst annual changes throughout the study period had a weaker influence. We conclude that both spatial and temporal patterns are driven primarily by temperature, with only a weak influence of available elevational area. This study is the first to describe the spatio‐temporal distribution of a suite of community‐level metrics along an elevational gradient and implies that temporal variation should be considered more carefully in studies of invertebrate diversity, particularly with respect to elevation and the mechanisms that may be maintaining diversity patterns.